태블릿 PC에 대한 소비자의 브랜드 태도와 인지 감성 요소가 구매의도에 미치는 영향 연구 - 아이패드와 갤럭시탭을 중심으로 - 박정서; Park Jeong Seo; 주대원; Joo Deh Won (한국디자인포럼, 2025)
연구배경 태블릿 PC는 일상과 업무에 필수적인 도구로 자리 잡았으며, 구매 결정에는 기능뿐 아니라 브랜드 태도와 감성적 경험도 큰 영향을 미친다. 따라서 본 연구는 태블릿 PC 시장에서 브랜드 태도와 인지 감성 요소가 소비자의 구매의도에 미치는 영향을 분석하는 것을 목적으로 진행하였다. 연구방법 태블릿 PC의 대표 제품인 아이패드와 갤럭시탭 사용자 중 20대 소비자 113명을 대상으로 설문조사를 실시하였다. 통계분석은 두 태블릿 PC 유형 간의 차이를 분석하기 위해 t검정을 활용하였으며, 구매의도에 미치는 영향을 분석하기 위해 단순 및 다중 회귀분석을 활용하였다. 연구결과 태블릿 PC 유형에 따라 브랜드 태도, 인지 감성 요소, 구매의도에서 유의미한 차이가 나타났고, 아이패드 사용자가 갤럭시탭 사용자보다 이를 더 높게 지각했다. 브랜드 태도와 복합적 감성이 구매의도에 가장 큰 영향을 미쳤으며, 그 뒤를 이어 인지적 감성과 기능적 감성이 영향을 미치는 것으로 나타났다. 반면, 감각적 감성과 문화적 감성은 유의미한 영향을 미치지는 않았다. 결론 아이패드 사용자는 갤럭시탭 사용자보다 브랜드태도와 감성적 가치를 더 높게 인식하였으며, 특히 브랜드 태도와 복합적 감성이 구매의도에 가장 큰 영향을 미쳤다. 이는 감성적, 상징적 가치가 소비자의 구매 행동에 핵심적 역할을 한다는 점을 시사하며, 기업이 차별화된 마케팅 전략과 감성적 경험 강화를 통해 시장 경쟁력을 높여야 한다는 것을 알 수 있다. Background Tablet PCs have become essential tools for daily life and work. In addition to functionality, this study focused on the influence of brand attitude, such as perceived quality and trust, and emotional factors, including pleasure and arousal, on purchase decisions in the tablet PC market. Methods A survey targeted 113 consumers in their 20s who used iPads and Galaxy Tabs. Statistical analysis used t-tests to analyze the differences between the two tablet PCs and regression analysis to analyze the influence on purchase intentions. Result The significant differences in brand attitudes, cognitive and emotional factors, and purchase intentions between iPad and Galaxy Tab users suggest that these factors play a crucial role in shaping consumer behavior. The higher perception of these factors among iPad users indicates a stronger brand loyalty and emotional attachment, which in turn influences their purchase intentions. Conclusion iPad users perceived brand attitude and emotional value more highly than Galaxy Tab users, and in particular, brand attitude and complex emotions had the greatest impact on purchase intention. This suggests that emotional and symbolic values are key to consumers’ purchasing behavior. It shows that companies should increase their market competitiveness through differentiated marketing strategies and strengthening emotional experiences.